TOP1α suppresses lateral root gravitropism in Arabidopsis - Hao Zhang; Ziyan Tang; Ying Zhang; Lin Liu; Dan Zhao; Xigang Liu; Lin Guo; Jingao Dong (Plant Signaling & Behavior, 2022)
Root gravitropism is important for anchorage and exploration of soil for water and nutrients. It affects root architecture, which is one of the elements that influence crop yield. The mechanism of primary root gravitropism has been widely studied, but it is still not clear how lateral root gravitropism is regulated. Here, in this study, we found that Topoisomerase I α (TOP1α) repressed lateral root gravitropic growth, which was opposite to the previous report that TOP1α maintains primary root gravitropism, revealing a dual function of TOP1α in root gravitropism regulation. Further investigation showed that Target of Rapamycin (TOR) was suppressed in columella cells of lateral root to inhibit columella cell development, especially amyloplast biosynthesis. Our findings uncovered a new mechanism about lateral root gravitropism regulation, which might provide a theoretical support for improving agricultural production.